2012
DOI: 10.1071/as11069
|View full text |Cite
|
Sign up to set email alerts
|

AMS Applications in Nuclear Astrophysics: New Results for 13C(n,γ) 14C and 14N(n,p) 14C

Abstract: Abstract:The technique of accelerator mass spectrometry (AMS) offers a complementary tool for studying long-lived radionuclides in nuclear astrophysics: (1) as a tool for investigating nucleosynthesis in the laboratory; and (2) via a direct search of live long-lived radionuclides in terrestrial archives as signatures of recent nearby supernova-events. A key ingredient to our understanding of nucleosynthesis is accurate crosssection data. AMS was applied for measurements of the neutron-induced cross sections 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…These test runs were also used to study whether the highly enriched 13 C sample gave rise to an enhanced AMS background compared to measurements on natural graphite (which is assumed to be 14 C-free). It could be demonstrated that the amount of 14 C produced in the activations at keV neutron energies was high enough that this background did not jeopardize the final uncertainties [38,43,44].…”
Section: B Ams Measurementsmentioning
confidence: 98%
See 1 more Smart Citation
“…These test runs were also used to study whether the highly enriched 13 C sample gave rise to an enhanced AMS background compared to measurements on natural graphite (which is assumed to be 14 C-free). It could be demonstrated that the amount of 14 C produced in the activations at keV neutron energies was high enough that this background did not jeopardize the final uncertainties [38,43,44].…”
Section: B Ams Measurementsmentioning
confidence: 98%
“…The list of reaction products of interest for astrophysics includes radioisotopes over the entire mass range, e.g., 10 Be, 14 C, 26 Al, 36 Cl, 41 Ca, 55 244 Pu. The present AMS measurements have been performed at the Vienna Environmental Research Accelerator (VERA) which represents a state-of-the-art AMS facility based on a 3-MV tandem [42,43]. A schematic view of the VERA facility is shown in Fig.…”
Section: Accelerator Mass Spectrometrymentioning
confidence: 99%
“…Recently, we have applied AMS for studying the production of 55 Fe in stellar nucleosynthesis [5,13,14]. Additional applications comprise detailed studies of 55 Fe production in a fusion environment: via fast neutron induced reactions on 58 Ni and 56 Fe, 55 Fe is produced through (n,a) and (n,2n) reactions, respectively [6,15].…”
Section: Introductionmentioning
confidence: 99%
“…Such conditions are achieved if the isobar does not form stable negative ions either as an atomic ion or as a suitably-chosen molecular species; well-known examples are e.g. analyzing 14 C À , 26 Al À , 129 I À , or 41 CaH À 3 , respectively, and similarly the radioisotopes in the mass range above Pb.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy, which is important for the role of 13 C as an s-process neutron poison, was studied using the activation technique [53]. The samples were irradiated at the Karlsruhe Institute of Technology in the quasi-stellar neutron spectrum for the direct determination of the MACS at kT = 25 keV, and also using neutron spectra with 123 and 178 keV mean energy to investigate the e↵ect of the 143 keV resonance.…”
Section: C: a Potential Neutron Poisonmentioning
confidence: 99%